Electric energy storages – a method for specification, design and assessment. (1st January 2013) - Schaede, Hendrik; Von Ahsen, Anette; Rinderknecht, Stephan; Schiereck, Dirk
The energy transition towards a significantly increased use of renewable energies is confronted with numerous challenges. These include the development of efficient energy storage systems, which need to address the specific requirements of the application area. The present paper contributes to this debate with the specification, design and assessment-method (SDA-method). Based on a statistical analysis of the applications load profile, the specifications for the energy storage system are defined and the design process is conducted. This is demonstrated using the example of a kinetic energy storage system. The following assessment considers the energetic behaviour, life cycle costs as well as environmental impacts. In order to fully exploit the comprehensive methodology, in-depth information is required. This relates firstly to the economical use of storages. Secondly, the multidimensional assessment is subject to many uncertainties. Our methodology reveals existing information gaps and helps to identify future research objectives.